THE INVESTIGATION OF DIMINUTIVES IN WORLD LINGUISTICS - Sarsenbaeva Qumarxan Mambetkerimovna, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article examines the study of diminutive units in world linguistics. The formation of diminutive units from a morphological point of view with the help of affixes is also emphasized.